Carabid beetle larva (Epomis) predation on Microhyla heymonsi with a review of predation by carabid beetles on amphibians - Evan S.H. Quah; Perry L. Wood, Jr; L. Lee Grismer; Robert E. Espinoza; Matthew L. Murdoch; Myint Kyaw Thura; Aung Lin (Herpetology Notes, 2023)
A novel report of predation by a larval carabid (Epomis sp.) on Microhyla heymonsi (Microhylidae) from Myanmar prompted us to conduct a comprehensive review of predation by carabid beetles and their larvae on amphibians. A total of 18 beetle species representing 14 genera have been recorded to consume salamanders and frogs from 37 species in 30 genera of 19 families. Reports of predation by carabid beetles on amphibians exist from every continent where amphibians occur.